2019
DOI: 10.1002/sd.1975
|View full text |Cite
|
Sign up to set email alerts
|

Are the Sustainable Development Goals self‐consistent and mutually achievable?

Abstract: On September 18, 2015, the United Nations General Assembly adopted the 2030 Agenda for Sustainable Development, which sets out wide‐ranging ambitions for global development. In response to the 2030 Agenda, the International Council for Science (ICSU), in partnership with the International Social Science Council (ISSC), subsequently published a detailed commentary on the Sustainable Development Goals (SDGs) and the linkages between them. The ICSU–ISSC Report raises the possibility that the SDG framework as a wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
62
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 22 publications
6
62
1
1
Order By: Relevance
“…Specifically, most recent TYNs also focus particularly on advancing the UN SDGs agenda (see Table 1 and Ref (Gad, 2009)). While in principle the SDGs seem highly interconnected, weighted network linkage analysis showed that there is a great asymmetry between SDGs 1-3 and the remaining goals (Dawes, 2020). Under this model, concentrating global efforts in SDGs 4-16 strongly impact SDGs 1-3, although there is little correlation in the opposite direction.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Specifically, most recent TYNs also focus particularly on advancing the UN SDGs agenda (see Table 1 and Ref (Gad, 2009)). While in principle the SDGs seem highly interconnected, weighted network linkage analysis showed that there is a great asymmetry between SDGs 1-3 and the remaining goals (Dawes, 2020). Under this model, concentrating global efforts in SDGs 4-16 strongly impact SDGs 1-3, although there is little correlation in the opposite direction.…”
mentioning
confidence: 88%
“…Emotional intelligence (and concomitantly empathy) as well as leadership skills are among the key cross-functional skills required for the future jobs (The Future of Jobs Report 2018) and, hence, experiential education on these areas are quite important for the TYNs members development. Moreover, as these networks advance educational skills globally they may indirectly impact SDGs 1-3 (Dawes, 2020). In addition, as they focus on promoting projects aligned with all UN SDGs, it implies that they can have a vast impact on the agenda.…”
mentioning
confidence: 99%
“…Complex systems research on the United Nations Sustainable Development Goals demonstrates that prioritising social justice will create wins for biodiversity (Bennett et al 2019;Dawes 2019). Being able to incorporate understandings from multiple knowledge systems is vital for a thorough understanding of the natural world (Allen et al 2014), and therefore critical in advancing ecology in Aotearoa.…”
Section: The Future Of Mātauranga In Ecologymentioning
confidence: 99%
“…From what we know about health inequality, linear, siloed approaches to solutions will not work. More than this, a reified understanding of interactions between and among goals is not sufficient for effective action [82]. Rather, action needs to happen on real systems focused on real interactions in the context of system behaviour-real human systems that exhibit emergence, feedbacks and sensitivity to initial conditions.…”
Section: Lessons For the Sustainable Development Goals (Sdgs)mentioning
confidence: 99%